Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12917-022-03176-w
|View full text |Cite
|
Sign up to set email alerts
|

Basics for the potential use of saliva to evaluate stress, inflammation, immune system, and redox homeostasis in pigs

Abstract: The use of saliva as a biological sample has many advantages, being especially relevant in pigs where the blood collection is highly stressful and painful, both for the animal and the staff in charge of the sampling. Currently one of the main uses of saliva is for diagnosis and detection of infectious diseases, but the saliva can also be used to measure biomarkers that can provide information of stress, inflammation, immune response and redox homeostasis. This review will be focused on the analytes that can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 70 publications
2
77
0
Order By: Relevance
“…Analyses of saliva samples are gaining growing importance in pigs as a sample to evaluate health status since they can be collected by non-invasive procedures and with less stress compared to venipuncture [ 19 ]. In the previous studies about the inflammatory response triggered by the repeated administration of LPS [ 20 ] or the local application of turpentine [ 21 ], acute-phase proteins (e.g., C-reactive protein and haptoglobin) and stress indicators (e.g., cortisol) were reliably detected in saliva samples.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of saliva samples are gaining growing importance in pigs as a sample to evaluate health status since they can be collected by non-invasive procedures and with less stress compared to venipuncture [ 19 ]. In the previous studies about the inflammatory response triggered by the repeated administration of LPS [ 20 ] or the local application of turpentine [ 21 ], acute-phase proteins (e.g., C-reactive protein and haptoglobin) and stress indicators (e.g., cortisol) were reliably detected in saliva samples.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, a comprehensive panel of 29 analytes was measured in saliva from fattening pigs that were serially monitored throughout their productive cycle. These analytes have been previously described in other studies [ 13 , 14 ], but the evolution of this profile of analytes during fattening has not been evaluated. The knowledge of how biomarkers could change during the different phases of fattening would be of interest for an adequate interpretation of the results and will contribute to a wider use of these analytes for the evaluation of pig health and welfare in farm conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Redox homeostasis can be assessed by measuring oxidants such as hydrogen peroxide (peroxide-activity Pox-Act, also known as H 2 O 2 ), reactive oxygen-derived compounds (d-ROMs) and the advanced oxidation protein products (AOPP), or antioxidants molecules such as cupric reducing antioxidant capacity (CUPRAC), ferric reducing ability of saliva (FRAS), and uric acid (UA). Finally, sialochemistry can include analytes related with the metabolic performance of the organism or with different tissues and organs, which are routinely measured in blood such as total protein (TP), urea, creatinine, glucose, lactate, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (FAL), lactate dehydrogenase (LDH), creatine kinase (CK), γ-glutamil transferase (GGT), calcium (Ca) and phosphorous (P) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of saliva for the determination of biomarkers has gained special attention in the last decade due to its easy collection, being of particularly high interest in pigs, in which blood collection is highly stressful. In addition, it has been shown that the saliva matrix is appropriate for health monitoring and disease diagnosis [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%